Investigation of Shear Strength and Microstructure Formation of Joined Ni Superalloys Using Ni Nanopastes - Benjamin Sattler; Susann Hausner; Guntram Wagner (Nanomaterials, 2022)
By using Ni nanoparticles, the bonding of Ni base superalloys can be achieved with shear strengths well above 200 MPa in a joining process at comparatively low temperatures between 675 °C and 975 °C. This is enabled due to the high surface-to-volume ratio of nanoparticles, which leads to distinctly lower melting and sintering temperatures than those of the corresponding bulk material. The nanoparticles in this study are employed in high-metal nanopastes, whereby different chemical compositions of the pastes and different sizes of Ni nanoparticles were investigated. The results for the joining of Ni base superalloys showed that both size and composition had a significant influence on the achievable strengths. In addition, an extensive examination was conducted to reveal the influence of the process parameters joining temperature, holding time and joining pressure on the shear strengths as well as microstructure. It was shown that the temperature exerted the most influence on the strengths and the microstructure. The joining pressure also had a significant influence. The holding time, on the other hand, did not have a major influence on the strengths and in some cases even showed an unexpected behavior, as the values decreased for some combinations with longer holding time.